1974
DOI: 10.4319/lo.1974.19.2.0249
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid uptake by marine phytoplankters1,2

Abstract: Axenic cultures of 25 species of unicellular marine algae were tested for their ability to utilize nine common amino acids, supplied at high concentrations in batch culture, as a nitrogen source; most species were able to use several amino acids, although growth was often slower than on nitrate nitrogen.The algae were also tested for their ability to t,ake up '"C-labclcd amino acids supplied at low, natural concentrations. In most cases, species that could grow on an amino acid at high concentration in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(71 citation statements)
references
References 17 publications
(3 reference statements)
5
65
1
Order By: Relevance
“…Although DFAAs represent a small fraction of DON produced by phytoplankton (13 to 30 O/O: Braven et al 1984), their rate of uptake and their rSle as nutrients for phytoplankton and bacteria are well documented (e.g. Crawford et al 1974, Wheeler et al 1974, Fuhrman 1987. In particular, GLU and GLN are known to be rapidly and selectively utilized by bacteria (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Although DFAAs represent a small fraction of DON produced by phytoplankton (13 to 30 O/O: Braven et al 1984), their rate of uptake and their rSle as nutrients for phytoplankton and bacteria are well documented (e.g. Crawford et al 1974, Wheeler et al 1974, Fuhrman 1987. In particular, GLU and GLN are known to be rapidly and selectively utilized by bacteria (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of cell death in bacteria and algae suggests that this phenomenon arose early in evolutionary history. Although the occurrence of bacterial and protozoan cell death has fostered the idea that it is adaptive or "altruistic" in the sense that surviving cells benefit from the organic compounds released by dying ones (Yarmolinsky 1995;Welburn et al 1997), autolysis in an obligate autotroph such as Dunaliella (which cannot benefit from organic molecules; see Wheeler et al 1974) would require a very different interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have shown that both groups of organisms can use either organic or inorganic forms of nitrogen as their sole nitrogen source (Brown 1980;Wheeler et al 1974). Our major interest from an ecological viewpoint was to determine the major sources for heterotrophic bacteria in natural populations.…”
Section: Discussionmentioning
confidence: 99%